2007
DOI: 10.1021/ma062649f
|View full text |Cite
|
Sign up to set email alerts
|

Toward Controlled Gilch Synthesis of Poly(p-phenylenevinylenes):  Synthesis and Thermally Induced Polymerization of α-Bromo-p-quinodimethanes

Abstract: It is general consensus that in Gilch polymerizations the 1,4-bis(halomethylene)benzene starting material first changes into an R-halo-p-quinodimethane intermediate which then acts as the real active monomer in the subsequent chain growth process. Recently, we could verify the formation of R-chloro-p-quinodimethane directly via in-situ NMR spectroscopy at low temperatures. However, quantitative formation of this pquinodimethane was not possible there. Now, we show that even such quantitative conversion into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 17 publications
1
62
1
Order By: Relevance
“…This is certainly a sound argument, independent of the fact that we are not in agreement with the offered explanation of why the PPV chains might be shorter in the presence of the mentioned additives: an anionic propagation mechanism was assumed for the Gilch polymerization, and the additives were believed to act as additional carbanionic initiators after their in-situ deprotonation (option A in Scheme 1). In contrast to this, we [20][21][22][23] and others [14,24] are convinced that this polymerization is based on radical chain growth. Nevertheless, for this latter option there is also a way available to explain the decreasing PPV chain lengths with increasing quantities of monofunctional benzylhalogenides: the mentioned additives are known to act as chain-transfer agents in radical polymerizations through their mobile benzylic hydrogen atoms (option B in Scheme 1).…”
Section: Communicationmentioning
confidence: 72%
“…This is certainly a sound argument, independent of the fact that we are not in agreement with the offered explanation of why the PPV chains might be shorter in the presence of the mentioned additives: an anionic propagation mechanism was assumed for the Gilch polymerization, and the additives were believed to act as additional carbanionic initiators after their in-situ deprotonation (option A in Scheme 1). In contrast to this, we [20][21][22][23] and others [14,24] are convinced that this polymerization is based on radical chain growth. Nevertheless, for this latter option there is also a way available to explain the decreasing PPV chain lengths with increasing quantities of monofunctional benzylhalogenides: the mentioned additives are known to act as chain-transfer agents in radical polymerizations through their mobile benzylic hydrogen atoms (option B in Scheme 1).…”
Section: Communicationmentioning
confidence: 72%
“…In order to keep the NMR spectra as simple as possible, we avoided aromatic substituents and focused our investigations on 5-methoxy-2-(b-ethylhexyloxy)-1,4-bis(chloromethylene)benzene 1a and 2,5-bis(bethylhexyloxy)-1,4-bis(bromomethylene)benzene 1b as the standard starting materials (Figure 2). [64,65,67] For comparison purposes, their 2,5-dihexyloxy-substituted (1c) and 2,5-bis(b-ethylhexyl)-substituted counterparts (1d) were also tested in some experiments, which bear linear and oxygen-free solubilizing side chains, respectively. The alkyloxy-substituted starting materials are easily available by the treatment of either hydroquinone 5 or hydroquinone monomethyl ether 6 with the corresponding alkyl bromide and potassium hydroxide, followed by the introduction of either two chloromethylene or two bromomethylene functional groups through twofold halomethylation (Scheme 5).…”
Section: Standard Starting Materials and Proceduresmentioning
confidence: 99%
“…Instead, all models resulted in an essentially unchanged process of spontaneous dissociation. Thus, it was not possible to identify a single stable molecular geometry of an anionic [64] intermediate, nor any corresponding transition state, for the anionic mode of the Gilch polymerization. It must be concluded that the formation of p-quinodimethanes 3 does not represent a step-wise E 1cb (or E 1 ) elimination, but follows a concerted E 2 -type mechanism for this 1,6-elimination.…”
Section: The Anionic Chain-growth Hypothesismentioning
confidence: 99%
See 2 more Smart Citations